Analysis of 6 pediatric nephrotic syndrome cases with complications of cerebral sinovenous thrombosis and literature review - Lu, Xuan; Yan, Cao; Chen, Hui; Wu, Xiaochuan (Frontiers in Pediatrics, 2023)
Background: Cerebral venous sinus thrombosis (CVST) is a rare but serious complication of nephrotic syndrome (NS) in children.To investigate the clinical characteristics of CVST in children with NS in order to timely diagnose this complication and reduce poor outcome.Methods: Collect and analyze clinical data and magnetic resonance venography (MRV) results of children with NS complicated with CVST.Results: Data of 6 patients with NS complicated with CVST were collected.4 of the patients were steroid-sensitive nephrotic syndrome (SSNS) and 2 were steroidresistant nephrotic syndrome (SRNS). The occurrence of CVST was observed within a time frame ranging from 12 days to 3 years following the diagnosis of NS. One patient had two episodes of thrombosis in three years, while the other five patients had only one episode of thrombosis. All patients had proteinuria at the time of episode of thrombosis. All patients presented with headache, and three of them had strabismus, seizures, and transient blindness, respectively. Neurological examination was negative. All patients were diagnosed with CVST by MRV within 3 to 16 days of the onset of headache. Two patients had TRPC6 gene mutation. All patients had resolution of neurological symptoms after anticoagulation treatment.Conclusion: CVST may occur in the early stages of NS. There is currently a lack of specific diagnostic indicators to reliably identify the presence of CVST in patients with NS. Children with NS who have neurological symptoms should be promptly evaluated with imaging studies. Whether TRPC6 gene mutation is also a risk factor for CVST remains to be further studied.